Incentives and subsidies for farmer adoption of food safety technologies - Hoffmann, Vivian; Jones, Kelly M. (International Food Policy Research Institute, 2017)
Unsafe food is a major cause of disease in developing countries, accounting for an estimated 2 million deaths per year globally and comprising a burden of illness comparable to that of malaria or tuberculosis (WHO, 2015). Reducing the risk of foodborne disease typically requires improvements in food production, processing, and handling practices from farm to fork. However, inducing these changes in the absence of effective regulatory enforcement is challenging because food safety is unobservable and is generally not rewarded by higher prices in markets. In Kenya, a prominent public health concern is contamination of maize, a major staple crop, with the fungal byproduct aflatoxin.